Research on Application of Sintering Basicity of Based on Various Intelligent Algorithms - Song Qiang; Zhang Hai-Feng (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Prediction of alkalinity in sintering process is difficult. Whether the level of the alkalinity of sintering process is successful or not is directly related to the quality of sinter. There is no good method, prediction of alkalinity by high complexity, the present nonlinear, strong coupling, high time delay, so the recent new technology, grey least square support vector machine have been introduced. In this paper, The weight of evaluation objectives has not given the corresponding consideration when solving the correlation degree by taking traditional grey relation analysis and it is with a lot of subjective factors, easily lead to mistakes in decision-making on program. What is more,a kind of alkaline grey support vector machine model, enables us to develop new formulations and algorithms to predict the alkalinity. In the model,